Novel targets to cure primary myelofibrosis from studies on Gata1low mice. Issue 1 (21st November 2019) - Zingariello, Maria; Martelli, Fabrizio; Verachi, Paola; Bardelli, Claudio; Gobbo, Francesca; Mazzarini, Maria; Migliaccio, Anna Rita
Abstract: In 2002, we discovered that mice carrying the hypomorphic Gata1 low mutation that reduces expression of the transcription factor GATA1 in megakaryocytes ( Gata1 low mice) develop myelofibrosis, a phenotype that recapitulates the features of primary myelofibrosis (PMF), the most severe of the Philadelphia‐negative myeloproliferative neoplasms (MPNs). At that time, this discovery had a great impact on the field because mutations driving the development of PMF had yet to be discovered. Later studies identified that PMF, as the others MPNs, is associated with mutations activating the thrombopoietin/JAK2 axis raising great hope that JAK inhibitors may be effective to treat the disease. Unfortunately, ruxolitinib, the JAK1/2 inhibitor approved by FDA and EMEA for PMF, ameliorates symptoms but does not improve the natural course of the disease, and the cure of PMF is still an unmet clinical need. Although GATA1 is not mutated in PMF, reduced GATA1 content in megakaryocytes as a consequence of ribosomal deficiency is a hallmark of myelofibrosis (both in humans and mouse models) and, in fact, a driving event in the disease. Conversely, mice carrying the hypomorphic Gata1 low mutation express an activated TPO/JAK2 pathway and partially respond to JAK inhibitors in a fashion similar to PMF patients (reduction of spleen size but limited improvement of the natural history of the disease). These observations cross‐validated Gata1 low mice as a bona fide animal model for PMF and prompted the use of this model to identify abnormalities that might be targeted to cure the disease. We will summarize here data generated in Gata1 low mice indicating that the TGF‐β/P‐selectin axis is abnormal in PMF and represents a novel target for its treatment.